Nutrition and Dietary Intake of Adolescent Girls in Indonesia: A Systematic Review - Musfira, Musfira; Hadju, Veni (Scripta Medica, 2024)
Adequate food and nutrient intake in adolescence is key to optimising adolescent nutritional status. Previous systematic studies that have been conducted on adolescents have generally found that Indonesian adolescents consume inadequate amounts of protein, fruits and vegetables. Aim of this study was to analyse most recent nutritional status in Indonesian adolescent girls analysed by region (urban-rural). The study was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. Two hundred thirty-nine articles were found, then 15 articles met the inclusion criteria and narrative analysis. Articles were assessed against a critical appraisal tool. Adolescent girls had varied energy and macronutrient intakes of calories (908.25 - 2125 kcal), protein (24.16 - 55.7 g), fat (21.89 - 64.29 g), carbohydrate (128.89 - 258.6 g) and fibre (3.88 - 4.9 g). The intake of adolescent girls based on residents (urban and rural) was found to be different. Urban adolescents had higher energy intake (1398.77 - 1815.57 kcal) with protein (41.42 - 80.81 g), fat (64.29 g), and carbohydrate (231.26 g). Rural adolescents had energy intake (1250.2 - 1365.8 kcal) with protein (36.21 - 65.42 g), fat (46.49 g) and carbohydrate (207.15 g). Micronutrient intake of adolescent girls found iron 2.64 mg, zinc 2.09 mg and vitamin C 71.75 mg intake in urban adolescent girls and 979.65 mg in rural adolescent girls. Snacks and fast food were frequently consumed, with frequency > 4x/week for urban (37.7 % snacks, 98.5 % fast food) and rural (46.2 % snacks, 93.5 % fast food) adolescents. Twenty-eight percent of adolescent girls tended to skip breakfast. Macronutrient and micronutrient intakes of adolescent girls were less than the nutritional adequacy of 70 % energy, 50 % protein, < 50 % fat and 86 % carbohydrate and were found to differ between adolescent girls in Urban and Rural areas.
Keywords: Micronutrient; Macronutrients; Food intake; Female adolescent